Sociodemographic profile of burn patients at a tertiary care hospital of Bundelkhand region of India - Saurabh Kumar Tiwari; Manish Jain; Satyendra Kumar; Amit Mohan Varshney; Sudhir Kumar (Wolters Kluwer Medknow Publications, 2020)
Background: Burns are a serious global public health concern. In India, every year, a substantial proportion of mortality and morbidity occurs due to burn injuries (1.4 lakh and 2.4 lakh, respectively). Burn injuries lead a significant medical, social, and psychological problem along with severe economic loss to individual and nation. A sociodemographic profile of burn patients is essential for the planning of program for the prevention of burns. The present study was conducted to study the sociodemographic profile of burn patients of Bundelkhand. Materials and Methods: Two hundred and fifty burn patients admitted consecutively between March 2018 and September 2018 in the burns unit of Maharani Laxmi Bai Medical College and Hospital, Jhansi, India, (Uttar Pradesh) were included in the present study. Sociodemographic data were obtained by the questionnaire as well as through the interview of patients and attendants. Results: The most affected age group, gender, and religion were 21-30 years (37.60%), female, (51.2%) and Hindus (92%), respectively. The common place of burn was home (88.4%) and maximum patients (75.2%) belonged to the rural areas. The floor cooking was most preferred method used for cooking (83.2%), and majority of patients were wearing synthetic clothes at the time of injury (51.2%). Psychiatric illness and suicidal tendency were present in only 6.8% of the patients. Regarding socioeconomic status, most of the patients (70.8%) belonged to the upper lower class. Thermal burns, electrical burns, and other (filigree and chemical) burns were more common in the married population, whereas scald was more common in unmarried population. Conclusion: All types of major burns were commonly occurred in the rural population, and they had poor educational and socioeconomic status. The incidence of burn injuries was mainly accidental in nature. Floor cooking is prevalent in Bundelkhand.